Konflik Batin Tokoh Asih dalam Cerpen Selasih Tak Lagi Sendiri Karya Kareematul Hayah - risky maysaroh; Vera Anggelina Nirmala Sari; Eva Dwi Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to find out the inner conflict experienced by the main character in the short story Selasih No Lagi Alone by Kareematul Hayah. The method used is a qualitative method considering that the author only relies on short stories in daily life in the Selasih No Lagi Alone section as a writing source. The approach method used is a hermeneutic approach, this research also uses data collection methods using reading techniques and note-taking techniques. The results of the research show that the inner conflict experienced by the character Asih in the short story Selasih Tak Lagi Alone by Kareematul Hayah is: First, sadness is an emotion characterized by feelings of misfortune, loss and helplessness. Second, anger is something that humans feel in the form of emotions or actions. Third, fear is a feeling that a person experiences with worry about something that is considered a threat to themselves. Fourth, Envy is a feeling of dissatisfaction or jealousy towards other people's success or happiness, achievements, negative feelings towards other people's luck. Inner conflict can be triggered by various things, namely family history, sadness experienced, a feeling of wanting to be like other people, feelings of lack of courage and loss of interest in carrying out activities that they can do